Characterizing the Clamor: An In-Depth Analysis of Inpatient Paging Communication. (July 2016) - Kummerow Broman, Kristy; Kensinger, Clark; Phillips, Charles; Fesseha, Betiel; Fill, Mary-Margaret; Borges, Nyal; Mathisen, Jason; Allen, Duncan; Land, Ed; Patel, Neal
Abstract : Purpose: Communication failures contribute to adverse clinical events and health care inefficiencies. Paged messaging remains a predominant communication mechanism at many academic medical centers. An interprofessional, institutionally sponsored initiative to improve inpatient care team communication sought to understand the content and quantity of paged messages. Method: A retrospective analysis at Vanderbilt University Medical Center was performed for messages delivered to the 15 highest-volume pagers carried by inpatient medical, surgical, and pediatric residents over two monthlong periods of data collection between November 2013 and February 2014. An interprofessional team defined message content categories a priori. Descriptive statistics were used to demonstrate message volume and distribution by content category. Team members and stakeholder groups discussed common message themes during and after categorization to identify targets for improving care efficiency. Results: During the data collection period, 10, 928 messages were paged (median 38 messages per pager per shift). The most common primary content categories were bedside nursing (2, 570; 30%) and medication (2, 285; 26%). Common bedside nursing communications included notification of vital signs (915; 36%), patient activity (481; 19%), and diet (444; 18%). Most medication messages were requests to start (1, 253; 55%) or change (694; 30%) a common medication. The team recommended implementing anticipatory orders for common medications and routine nursing staff needs using computerized order algorithms to reduce the volume of noncritical messages. Conclusions: An interprofessional assessment of the content and volume of paged communication identified high volumes of noncritical messages that could be eliminated through better anticipation of patient care needs.